Beckman competitors' potentiometer components - Armstrong & Hess (1950)
Beckman Instruments documented company-built instruments and electronic components, but in some cases also documented the work of competitors. These models were viewed as competitive to the Helipot Model 91.
Keywords: Passive components; Potentiometer